Horta escolar e educação ambiental: conexões com os objetivos de desenvolvimento sustentável - Rodrigues, Erica (2019)
Given the constant repressive action of the Military Police and other inspection agencies, which results in punitive fines, but does not allow the reversal of damage to the environment, it is important to take steps that contribute to the awareness of the need for prevention and environmental preservation, as well as on the sustainable use of natural resources, which clearly points to the importance of measures aimed at achieving the 17 sustainable development goals proposed by the UN in 2015. Caring for the environment is everyone's responsibility and need. So it is necessary to develop in the children from an early age the culture of caring for the planet, and schools, with the ideal social space for this, seek to do so through theoretical and practical activities. It is known that in Brazil the cultivation of vegetable gardens is something cultural and widespread among the population. Whether for educational purposes or for consumption, vegetable gardens are present in schools, and have been applied as a practical tool for environmental education, where the whole school community can benefit from the teachings and knowledge that reside there.The present work aimed to investigate the situation of school gardens in the municipality of Marechal CândidoRondon - PR, as well as to verify whether the vegetable gardens are actually used for environmental education in the municipality, and to analyze and compare the results between urban and rural schools. To meet the proposed objectives the data collection instrument was a questionnaire, applied to the principals, teachers and pedagogical staff of the urban and rural schools of the municipal elementary school. The results were treated by content analysis and showed that it is a There is a consensus among education professionals that children more easily incorporate learning into practical classes, and that a vegetable garden is an ideal tool when it comes to teaching about land-care skills, healthy eating, sustainability of natural resources, and others.This study concluded that urban schools still have the most limited resources needed to maintain vegetable gardens, especially due to the lack of space and manpower. Rural schools, in turn, are the ones that use vegetable gardens the most as a pedagogical tool, while all rural schools in the municipality do so, while only 40% of urban schools are able to maintain the vegetable gardens. The presence of vegetable gardens in schools, especially their use in education and healthy eating, connects with the UN's 17 sustainable development goals, as it promotes, through simple actions, values directly linked to the sustainability areas of the agenda.